Pemeriksaan Pajak Berdasarkan Analisis Kewajaran Usaha Sawit Sesuai SE-27/PJ/2017 - Hendri Sopian (Politeknik Keuangan Negara STAN, 2023)
Tax disputes as a result of tax assessments issued by the Directorate General of Taxes (DGT) are currently relatively increasing, especially in the palm oil business sector. In several cases of tax disputes over tax assessments issued based on an Appraisal Report made by the DGT Appraisal Team according to the technical guidelines in the Director General of Taxes Circular Letter Number SE-27/PJ/2017, there have been variations in appeal decisions. This research uses a normative-empirical analysis approach. The results of the study show that tax assessments issued immediately are only based on the results of the DGT Appraisal Team according to SE-27/PJ/2017 in tax audit activities, namely the Panel of Judges wins the DGT in the event that the Taxpayer is uncooperative in lending documents/if the bookkeeping is declared invalid by The DGT Audit Team cannot be used to calculate the tax payable. While the decision in favor of the taxpayer is if the taxpayer has been cooperative and provided all the data requested by the DGT during the audit, but the DGT cannot prove the link between the results of the Assessment by the DGT Appraisal Team and the books/data provided by the taxpayer. Therefore, the need for proper application by DGT's internal ranks of the guidelines in SE-27/PJ/2017 in order to optimize state revenue.